Blind detection for image steganography using short du ate codes statistical model for Hilbert scanning sequences - Shang-ping ZHONG; Qiao-fen XU; Wen-zhong GUO; Bin LIAO (Tongxin xuebao)
By analyzing and proving the correlation between the detection capability of a short duplicate code statistical feature and the probability of cumulating short duplicate codes、the dimension of short duplicate codes,a method to improving the detection capability of a short duplicate code statistical feature was found.Then,a blind detection method for image steganography using short duplicate codes statistical model for Hilbert scanning sequences was proposed.The proposed method used Poisson distribution test to detect the stego-message based on the statistical feature of short duplicate code with same elements in LSB Hilbert scanning sequences.So,the proposed method could make full use of Hilbert curve to maintain the good properties of local correlation,and could not only use the correlation of adjacent elements,but also use the correlation of elements in local regions.Theoretical lysis and experiments show that the proposed method can effectively improve the detection rate under the condition of effectively controlling the false alarm rate.